Relationship between Occupation and Mother's Knowledge of Toddler Development and Stunting at Dabun Gelang Health Center, Dabun Gelang District, Gayo Luwes Regency in 2021 - Maya Sari; Cut Sari Dewi (Institute of Computer Science (IOCS), 2022)
Malnutrition occurs since the baby is in the womb and in the early days of birth, but stunting only appears after the child is 2 years old (Kemenkeu, 2018). Children who experience stunting can experience impaired physical, mental, cognitive and intellectual development so that children are not able to learn optimally. Stunting children have low cognitive abilities, if not treated before reaching the age of five years, they can have an impact until adulthood and are at risk of death and will give birth to children with low birth weight (Soetjiningsih, 2013). The purpose of this study was to determine the relationship between mother's knowledge and work regarding the growth and development of toddlers with the incidence of stunting at the Dabun Gelang Health Center, Dabun Gelang District, Gayo Luwes Regency in 2021. The type of research conducted is descriptive analytical, the population in the study is 578 people and a sample of 57 people is taken, using Accidental Sampling. The data collected in the study is primary data, namely data obtained directly from respondents. The data analysis used is univariate analysis and bivariate analysis. The results of the study were that the majority of respondents lacked knowledge as many as 31 (54.4%) respondents with short stunting, 23 (40.3%%) respondents. From the results of statistical tests obtained P value of 0.003 <0.05, which means that there is a relationship between mother's knowledge about growth and development of toddlers with stunting. the majority do not work as many as 30 (52.6%) respondents with short 25 (43.8%) respondents. From the statistical test results obtained P value 0.000 <0.05, which means that there is a relationship between the mother's work on the growth and development of children under five with the incidence of stunting. It is hoped that health workers at the Dabun Gelang Health Center can encourage and foster the community to better maintain health and improve the growth and development of toddlers so as to minimize the risk of stunting